Parent and Child Interaction Models in Islamic-Based Family Education - Susanti, Weti; Nurdin, Syafruddin; Wirman, Eka Putra (Indonesian Center for Religion and Society Studies (InTReSt), 2023)
In the context of Islamic teachings, religious education for children is the main obligation that parents must carry out before teaching children another knowledge. The choices and patterns of parents in educating children in the family are directly correlated with the child's religious habits. In fact, the religious formation of children must be taught as early as possible, in fact these religious habits must begin in the womb. In fact, this research aims to find out how parents and children interact in Islamic-based education. This research uses a qualitative method with a phenomenological approach, data sources were taken through in-depth interviews with seven informants, to strengthen the interview data the author also carried out direct observations to document various activities carried out by parents in educating their children in an Islamic way. All interview and observation data were analyzed using the Milles & Huberman interactive thematic analysis model technique. Research findings found a model of interaction between mother and child in the informant's family, such as putting the family in one system, seeing children as small adults. Models such as the findings of this research can be used as examples by Muslim families in educating and interacting with children